Prognostic role of the lymphocyte-to-monocyte ratio in patients undergoing resection for nonmetastatic rectal cancer. Issue 44 (November 2016) - Wu, Qing-Bin; Wang, Meng; Hu, Tao; He, Wan-Bin; Wang, Zi-Qiang
Abstract : Abstract: Lymphocyte-to-monocyte ratio (LMR) was associated with survival benefit in some types of cancer. The relationship between LMR and rectal cancer has not been investigated. We conducted a retrospective cohort study to assess the prognostic significance of LMR in patients with nonmetastatic rectal cancer. Patients with rectal cancer who underwent potentially curative resection between January 2009 and December 2013 were enrolled. The LMR was calculated from preoperative blood test by dividing the absolute lymphocyte counts by the absolute monocyte counts. The optimal cut-off value for LMR was calculated as the median value. On the basis of the cut-off value, patients were divided into 2 groups: low group and high group. A total of 543 patients with rectal cancer were eligible for this study. The median follow-up time for all patients was 55 months (range 6–85 months). The cut-off value of LMR was 5.13 and patients were divided into 2 groups: low group (LMR < 5.13) and high group (LMR ≥ 5.13). In the univariate and multivariate analysis, the LMR was not significantly associated with overall survival (OS) [hazard ratio (HR): 1.034, 95% confidence intervals (CIs): 0.682–1.566, P  = 0.876]. When disease-free survival (DFS) was compared, univariate and multivariate analysis also indicated that the LMR was not significantly associated with DFS (HR: 0.988, 95% CI: 0.671–1.453, P  = 0.950). In addition, in the subgroup analysis by tumor-node-metastasis stage, there existed no significance between LMR and OS and DFS. Although as an easy access and highly efficient laboratorial inflammatory marker, LMR cannot predict the prognosis of nonmetastatic rectal cancer patients.